Literature Review: Pengaruh Good Corporate Governance, Whistleblowing System, Dan Audit Internal Terhadap Pencegahan Kecurangan - Ana Nur Azizah (JURNAL ECONOMINA, 2024)
Basically, minimizing fraud can be done by preventing fraud itself, but reducing fraud alone is not enough. Therefore, it is necessary to detect fraud. This article reviews research on factors that influence fraud prevention, namely Good Corporate Governance, Whistleblowing Systems, and Internal Audit. The purpose of this literature review is to develop hypotheses about the influence between variables for use in further research. The preparation of this literature review article uses the library research method, where the data used comes from other academic online media. The results of this literature research are that Good Corporate Governance, Whistleblowing Systems, and Internal Audit have an influence on fraud prevention. This means that the better the Good Corporate Governance, Whistleblowing System and Internal Audit you have, the better the implementation in preventing fraud.